2013
DOI: 10.1002/cbdv.201300076
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Variability of Cleistopholis patens (Benth.) Engl. et Diels Leaf Oil from Ivory Coast

Abstract: The chemical composition of 48 leaf oil samples isolated from individual plants of Cleistopholis patens (Benth.) Engl. et Diels harvested in four Ivoirian forests was investigated by GC-FID (determination of retention indices), GC/MS, and (13) C-NMR analyses. The main components identified were β-pinene (traces-59.1%), sabinene (traces-54.2%), (E)-β-caryophyllene (0.3-39.3%), linalool (0.1-38.5%), (E)-β-ocimene (0.1-33.2%), germacrene D (0.0-33.1%), α-pinene (0.1-32.3%), and germacrene B (0-21.2%). The 48 oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As far as we know, no study has been reported in the literature on the chemical composition of P. oliveri essential oil. Within our ongoing work on the characterization of Ivoirian aromatic plants through the chemical composition of their essential oils , we were interested in P. oliveri leaf oil. The first analyses exhibited a complex essential oil with a composition dominated by sesquiterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, no study has been reported in the literature on the chemical composition of P. oliveri essential oil. Within our ongoing work on the characterization of Ivoirian aromatic plants through the chemical composition of their essential oils , we were interested in P. oliveri leaf oil. The first analyses exhibited a complex essential oil with a composition dominated by sesquiterpenes.…”
Section: Introductionmentioning
confidence: 99%